L’espace infini du brouillon dans les traductions collaboratives : Les Diaboliques de Boileau et Narcejac en italien - Ornella Tajani (Continents manuscrits)
By crossing the genetic perspective and the practice of collaborative translation, this article aims to explore a chapter draft of the Italian translation of Boileau-Narcejac’s novel Celle qui n’était plus (I Diabolici, translated by F. Di Lella and G. Girimonti Greco, Milano, Adelphi, 2014).Through the insertion of comments in their work file, the two translators develop a dialogue in the margin of the text, discussing the choices adopted, proposing other solutions as well as remarks on the interpretation of the scene in question.I will analyse what constitutes a real “discourse” about translation and classify these comments into different categories, in order to show that the study of drafts, revealing the translation process at the very moment it is being carried out, can be of great interest, all the more so in collaborative translations, where the need for exchange ends up leaving more obvious traces.